2019
DOI: 10.1016/j.csbj.2019.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Fast Methods for Prediction of Aldehyde Oxidase-Mediated Site-of-Metabolism

Abstract: Aldehyde Oxidase (AO) is an enzyme involved in the metabolism of aldehydes and N-containing heterocyclic compounds. Many drug compounds contain heterocyclic moieties, and AO metabolism has lead to failure of several late-stage drug candidates. Therefore, it is important to take AO-mediated metabolism into account early in the drug discovery process, and thus, to have fast and reliable models to predict the site of metabolism (SOM). We have collected a dataset of 78 substrates of human AO with a total of 89 SOM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 37 publications
0
32
0
Order By: Relevance
“…For the electronic properties like E LUMO , electronegativity, and hardness, there were no significant difference between substrates and nonsubstrates (Figure B,D). As for the ESP properties, several studies demonstrated that the partial charges such as MK charge or ESP partial charge of the metabolic sites, namely, the electron-deficient carbon adjacent to the nitrogen, were more positive than non-SOMs. ,, Because the ESP partial charge of the atom was the integral of electrostatic potential surface on the atom, and for the nitrogen-containing heterocycle rings, the more positive charge of the SOMs might implicate the higher value of the ESP energy. Thus, we speculated that the substrate might have higher maximum values of the ESP energies (Max_ElPot) on the electrostatic potential maps or the nonsubstrates might have lower minimum values of the ESP energies (MIN_ElPot) on the electrostatic potential maps.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…For the electronic properties like E LUMO , electronegativity, and hardness, there were no significant difference between substrates and nonsubstrates (Figure B,D). As for the ESP properties, several studies demonstrated that the partial charges such as MK charge or ESP partial charge of the metabolic sites, namely, the electron-deficient carbon adjacent to the nitrogen, were more positive than non-SOMs. ,, Because the ESP partial charge of the atom was the integral of electrostatic potential surface on the atom, and for the nitrogen-containing heterocycle rings, the more positive charge of the SOMs might implicate the higher value of the ESP energy. Thus, we speculated that the substrate might have higher maximum values of the ESP energies (Max_ElPot) on the electrostatic potential maps or the nonsubstrates might have lower minimum values of the ESP energies (MIN_ElPot) on the electrostatic potential maps.…”
Section: Resultsmentioning
confidence: 99%
“…Decision tree model DTN AOX (A) for predicting hAOX-mediated SOMs and its performance on (B) the test data set and (C) the external data set, compared with our previous DT AOX model and three descriptors proposed by Montefiori et al …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations